Impact of climate change on rice production: an empirical study in Kaski and Nawalparasi, Nepal (Journal of Agriculture and Natural Resources, 2021)
This study explores the relationship between climate variables to rice production in Kaski and Nawalparasi district of Nepal. The study was conducted in the year 2016. This study captured the time series data ranging from 1995 to 2014 on rice production, temperature and rainfall of two different districts and analyzed through panel data regression. Regarding primary data collection, a total of 120 sampled households were surveyed by using simple random sampling to understand the perception of farmers to change in climatic parameters using a semi-structured pre-tested questionnaire and Focus Group Discussions. The secondary information was collected from the Ministry of Agriculture and Livestock Development, Department of Hydrology and Meteorology and Centre Bureau of Statistics. The regression model revealed that seasonal rainfall had a linear relation on rice production (p